Prevalence and Direct Economic Losses from Bovine Tuberculosis in Makurdi, Nigeria - E. F. Ejeh; M. A. Raji; M. Bello; F. A. Lawan; M. I. Francis; A. C. Kudi; S. I. B. Cadmus (Veterinary Medicine International)
A retrospective study was conducted to investigate the prevalence of bovine tuberculosis and direct economic losses (DEL) from tuberculosis in cattle slaughtered in Makurdi abattoirs from 2008 to 2012, using abattoir records obtained from the Ministry of Agriculture and Natural Resources. Out of 61654 cattle slaughtered during the study period 1172 (1.90%) were positive for tuberculosis lesions. The annual prevalence of bovine tuberculosis ranges from 0.90% in 2008 to 4.04% in 2012. There was significant (P<0.05) difference in annual prevalence of bovine tuberculosis. It was also observed that there was no seasonal difference in the prevalence of bovine tuberculosis. A total of 1935 affected organs by BTB weighing 3046.50 kg, amounting to 2.91 × 106 Naira (1.82 × 104 USD), were condemned within the study period. Seasonal variation in organ condemnation due to bovine tuberculosis was significantly different (Mann-Whitney U statistics = 774 × 103, P=0.034). It was concluded that bovine tuberculosis is prevalent in Makurdi and accounts for heavy economic losses due to condemnation of edible organs.